Applied Research in Environmental Economics - Böhringer, Christoph.; Böhringer, Christoph.; Lange, Andreas.; Lange, Andreas. (ZEW Economic Studies,, 2005)
Sustainable development, climate policy, and biodiversity conservation are examples of issues on the current political agenda in many countries. These themes are also subject to economic research, and economic insights are increasingly finding their way into the design of environmental policy. Still, the reception of academic findings by policy makers as well as the timely identification of policy-relevant questions by economic researchers often seem to be problematic. This volume attempts to vitalise the exchange between policy makers and academics. It offers a snapshot of environmental economic research on a range of policy-relevant problems. Academic contributions are complemented by views of policy makers on priority fields in environmental policy, the usefulness of academic research for decision making, and requirements to applied research in the future.